On the policy of extending the provisions of the Towns Improvement Act (Ireland), 1854, to the towns still under the old Paving and Lighting Act, 9 Geo. IV c. 82 - Hancock, John (Statistical and Social Inquiry Society of Ireland, 1865)
The Towns Improvement Act of 1854 was a very important step in our local legislation. The great value of this act is shown by the extent to which it has been adopted, 76* towns having in ten years come under its provisions, whilst at the end of 25 years only 55 towns had adopted the provisions of the old paving and lighting act of George IV. My object in now addressing you is to contrast the leading points of the two acts, with a view of inducing the above-named towns to co-operate with the other towns of the country, and thus have a uniform system of municipal government throughout Ireland.
Read Tuesday, 31st January, 1865
Keywords: Towns Improvement Act 1854; Paving and Lighting Act 1828; Municipal government legislation in Ireland; 314.15